Modeling Systemic Policy Priorities in Community-Based Non-Formal Education: A Hybrid Delphi–ISM–ANP Approach in Indonesia - Saiful Hadi; Aang Kisnu Darmawan; Abd Ghofur; Elais Retnowati; Mohamad Zubaidi (SCAD Independent, 2026)
Community-Based Non-Formal Education (CB-NFE) in Indonesia continues to face structural challenges related to fragmented governance, policy inconsistency, and unstable operational funding, limiting its contribution to inclusive lifelong learning and community empowerment. This study aimed to identify critical development factors and determine strategic policy priorities to improve the sustainability of CB-NFE. The research employed a sequential hybrid approach integrating Delphi, Interpretive Structural Modeling (ISM), MICMAC, and Analytic Network Process (ANP). Data were collected through expert judgment involving 12 participants from academia, government institutions, and non-formal education practitioners. The findings revealed that policy synchronization and operational funding support functioned as the primary structural drivers of CB-NFE development, while tutor certification and professional development emerged as the most influential strategic leverage for improving broader systemic outcomes. These findings suggested that strengthening human capital can generate a greater systemic impact than isolated regulatory interventions. The study contributes to network-based policy analysis in non-formal education and offers strategic implications for strengthening community-based lifelong learning systems in decentralized governance contexts.